2011
DOI: 10.1148/radiol.11101559
|View full text |Cite
|
Sign up to set email alerts
|

MR-compatible Assistance System for Biopsy in a High-Field-Strength System: Initial Results in Patients with Suspicious Prostate Lesions

Abstract: Preliminary results indicate that MR-guided robot-assisted biopsy is feasible and can be performed safely with highly accurate cannula placement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
55
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(58 citation statements)
references
References 30 publications
2
55
0
1
Order By: Relevance
“…The duration of MRGB in a closed system with a transrectal examination at our institution (45 -55 min) is similar to the duration published in the literature (29 - teal examination. Applying this latter approach in a closed system, the procedure time required by Zangos and co-workers from the time of patient entry to the biopsy unit until completion was also 39 min, which is comparable to the results of our present study as well as those of previously chronicled examinations [19,28], albeit a reduction in intervention time has been observed in other studies due to acquired skill and improved efficiency [28]. In addition, needle-guided tracking systems and implementation of robotics may improve these limitations.…”
supporting
confidence: 90%
See 1 more Smart Citation
“…The duration of MRGB in a closed system with a transrectal examination at our institution (45 -55 min) is similar to the duration published in the literature (29 - teal examination. Applying this latter approach in a closed system, the procedure time required by Zangos and co-workers from the time of patient entry to the biopsy unit until completion was also 39 min, which is comparable to the results of our present study as well as those of previously chronicled examinations [19,28], albeit a reduction in intervention time has been observed in other studies due to acquired skill and improved efficiency [28]. In addition, needle-guided tracking systems and implementation of robotics may improve these limitations.…”
supporting
confidence: 90%
“…The advantage of a robotic device is that the patient does not have to be moved in and out of the MRI scanner during the biopsy session, which decreases the procedure time, enhances patient comfort, and improves needle positioning [26]. The examination methods used for robotic-assisted biopsies are transgluteal and transrectal, and the intervention time for these methods ranges between 39 min and 76 min [16,28,34]. A limitation of our study that should be reported is the inconsistent imaging protocol for the MRI examinations prior to biopsy.…”
mentioning
confidence: 99%
“…Much of this increased time is from repeatedly moving the patient out of the scanner to enable access to the needle, followed by repeat imaging. Some investigators have therefore looked at MR compatible robotic devices via rectal [32], gluteal [33] and perineal approaches [ 35,36] recently described an MR compatible mechatronic system for transperineal needle guidance ( Fig. 1).…”
Section: In-bore Prostate Biopsymentioning
confidence: 99%
“…Several teams have developed MRI-compatible robotsincluding ' Access to prostate tissue' (APT1 39 and APT2 40 ), UMCU (University Medical Centre Utrecht), 5 MrBot 41 (Figure 3), MRI-P 42 and Innomotion. 43 A standard for MRI-guided prostate intervention is an initial scan, performed with the robot at the footend of the table, to 'register' the co-ordinates of the robotic system in 3D space. Once this registration has taken place, two approaches have been proposed.…”
Section: Mri-integrated Robotic Systemsmentioning
confidence: 99%
“…The first of these uses manual needle insertion; in doing so, the patient must be taken out of the MRI scanner, which means the biopsy is not being performed with real-time imaging. [43][44][45] By contrast, the second approach uses automatic or telerobotic needle insertion, [44][45][46][47] which enables truly live MRI-guided biopsy. Automated needle insertion techniques include needle rotation and stepwise insertion (tapping).…”
Section: Mri-integrated Robotic Systemsmentioning
confidence: 99%